Analysis of Heavy Metals Concentration and Its Impact on Hepatic Indexes in Clarias gariepinus from Ibi, Gidin-Dorowa, and Donga Rivers in Taraba State, Nigeria - Asuelimen, Steve Osagie; Ale, Ebenezer Morayo; Umaru, Isaac John; Iheanacho, Chinedu Christian (African Journal of Biochemistry and Molecular Biology Research, 2024)
Exposure to heavy metals, which are particularly detrimental to human health, has increased as a result of anthropogenic activities and modern industry. Increased levels of heavy metals in African catfish (Clarias gariepinus) can be a good sign that human activity has contaminated an aquatic ecosystem. The study aimed to eval_uate the levels of heavy metals and their potential effects on hepatic indexes in Clarias gariepinus collected from three different rivers (Ibi, Donga, and Gindin Dorowa) in Taraba State, Nigeria. The fish samples were collected from the three different rivers during the dry season. The gills were removed from the fish and subjected to oven drying and grinding before being analyzed for heavy metal concentrations. Blood samples were also collected from the fish for liver biomarkers analysis. The heavy metal concentrations (specifically Pb, Cd, Zn, As, and Hg) were determined using Micro Plasma Atomic Emission Spectroscopy (MP-AES) and compared to the maximum levels specified by the World Health Organization (WHO). The results showed that zinc had the highest mean concentration in all three river samples. However, all heavy metal concentrations in the gills of the fish were found to be below the maximum allowed limits advised by standard bodies, indicating that the gills were safe for consumption. Also, the liver biomarker analysis showed higher levels of ALP, total bilirubin, and albumin activity in the fish from Gindin-Dorowa compared to Donga and Ibi. However, all liver biomarker values fell within the reference standards, indicating that the fish from the three rivers were free from heavy metal toxicity. In conclusion, the study suggests that the Clarias gariepinus samples from the three rivers in Taraba State, Nigeria, had concentrations of heavy metals within safe limits, as determined by the WHO. The liver biomarker analysis further supported the absence of heavy metal toxicity in the fish.